Growth and radioluminescence of metal elements doped LiCaAlF6 single crystals for neutron scintillator. (July 2016) - Tanaka, Chieko; Yokota, Yuui; Kurosawa, Shunsuke; Yamaji, Akihiro; Jary, Vitezslav; Babin, Vladimir; Pejchal, Jan; Ohashi, Yuji; Kamada, Kei; Nikl, Martin; Yoshikawa, Akira
Abstract: The ns 2 -type metal elements (Pb and Sn) doped LiCaAlF6 single crystals were grown by a micro-pulling-down (μ-PD) method. Pb doped LiCaAlF6 [Pb:LiCAF] crystals showed high transparency and single phase of the LiCAF structure. However, we could not obtain Sn:LiCAF crystals due to the evaporation of SnF2 during the crystal growth. There was an absorption peak around 193 nm in the transmittance spectrum of Pb:LiCAF crystal. In the radioluminescence spectrum of the Pb:LiCAF crystal under X-ray irradiation, two emission peaks around 200 and 830 nm were observed. Highlights: Pb 2+ doped LiCAF single crystals were grown by micro-pulling-down method. We measured powder XRD and transmittance of grown crystals. We revealed radioluminescence emission spectra under X-ray irradiation.